(untitled) (Research, Society and Development, 2022)
Introduction: There are technological resources that can contribute to the development of students, thus, the aim is: Conduct a bibliographic study to know which technological strategies were most used to continue teaching during the pandemic. Methodology: This is a literature review research. Data collection took place in July 2021, using the terms: Google Meet; Covid-19; Whatsapp; Digital Media in Teaching. After the refinement step, 14 articles remained that were part of the sample. Results and discussion: Google Meet which was the most used platform. Facebook WhatsApp was used as communication tools between teachers and students. Plus Google Classroom and Podcast Recording. One strategy that drew attention was the use of Instagram for Lives, whose tool allows classes to be saved on the social network’s IGTV, and can be viewed as many times as the student wants. This social media enables its users to have different experiences promoting engagement and collaborative educational practice. Final Remarks: Google tools were the most used, either because they are easy to access or because of free access. It was noticed that social networks were also exploited for teaching classes. Youtube also served the same purpose. WhatsApp, in addition to being a tool used for communication between teachers and students, was also used as a resource in classes.